2019
DOI: 10.1055/s-0039-1683845
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Design on Force between Flexor Tendons and Distal Radius Volar Plates

Abstract: Background Flexor tendon injury is a rare but serious complication of distal radius volar plating. Purpose This study aims to determine whether the design of distal radius volar plates impacts the amount of force exerted on the flexor digitorum profundus (FDP) and flexor pollicis longus (FPL) tendons when the plates are placed proximal and distal to the watershed line. Methods Three commercially available plates were applied to 10 fresh, matched-pair upper extremity specimens. Cyclical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Hinchcliff et al. 37 found that the volar plate design did not significantly impact either the mean or median force between the plate and the flexor tendons. However, Limthongthang et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hinchcliff et al. 37 found that the volar plate design did not significantly impact either the mean or median force between the plate and the flexor tendons. However, Limthongthang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, further research is needed. Hinchcliff et al 37 found that the volar plate design did not significantly impact either the mean or median force between the plate and the flexor tendons. However, Limthongthang et al 11 found that a plate with a Y-shaped design (the FPL plate), in which the bridging segment of the plate between the radial and intermediate columns had been removed, had a significantly smaller contact area between the plate and the FPL relative to other plates.…”
Section: Discussionmentioning
confidence: 99%